Management Students at School Value-Based Islamic Boarding Schools: A Comparative Study in Indonesia and Thailand - Luthfiah Syafiqi; Siti Mutholingah; Miss Fateemah Ali Muhammad (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2026)
This study aims to analyse and compare the planning, implementation, and evaluation of student management systems within Islamic boarding school-based institutions in two distinct Southeast Asian contexts: MTs Al-Hidayah in Indonesia and Mattayom Muslimeen Suksa in Thailand. As Islamic education faces the challenges of modernisation, understanding how these schools preserve traditional values while adopting formal management standards is crucial. This research employed a qualitative multi-case study design, utilising both within-case and cross-case analyses to identify similarities and divergent practices. Data were gathered through in-depth interviews, observations, and documentation, with informants selected via purposive sampling of 10 key participants, including school principals, teachers, and students from both institutions. The results demonstrate that both schools successfully integrate national curricula with Islamic boarding school values, emphasising character building and spiritual development. However, the study reveals significant contextual adaptations: MTs Al-Hidayah focuses on input quality through Al-Quran literacy assessments, while Mattayom Muslimeen Suksa prioritises social accessibility and inclusivity for Muslim minorities through scholarship programs. The primary contribution of this research is the identification of a sustainable, integrative student management model. This model features the integration of hybrid technology into admission planning, the seamless infusion of boarding school values into formal instructional processes, and continuous behavioural-academic evaluation. These findings offer a practical framework for other Islamic educational institutions to enhance the quality of their management without compromising their religious identity. This sustainable model serves as a strategic reference for school administrators navigating the complexities of managing student development across diverse socio-cultural environments